The right arrow symbol used to show the transition from a point to its image after a transformation is not contained within the Eq

Question

The right arrow symbol used to show the transition from a point to its image after a transformation is not contained within the Equation Editor. If such a symbol is needed, type “RightArrow.” For example: P(0, 0) RightArrow P′(1, 2).

Write a translation rule that maps point
D (7,−3) onto point D'(2,5).

in progress 0
Ngọc Diệp 1 month 2022-12-30T11:57:23+00:00 2 Answers 0 views 0

Answers ( 2 )

    0
    2022-12-30T11:58:57+00:00
    Answer:
    A(1,4)=A(1,-4)
    B(3,-2)=b(3,2)
    D(4,2)=D(4,-2)

    0
    2022-12-30T11:59:17+00:00
    Answer:
    The translation rule that maps point D ( 7 , − 3 ) onto point D ‘ ( 2 , 5 )
    is (x , y) → (x – 5 , y + 8)
    Step-by-step explanation:
    Let us revise the translation
    If the point (x , y) translated horizontally to the right by h units  then its image is (x + h , y)
    If the point (x , y) translated horizontally to the left by h units  then its image is (x – h , y)
    If the point (x , y) translated vertically up by k units  then its image is (x , y + k)
    If the point (x , y) translated vertically down by k units  then its image is (x , y – k)
    (x , y) → (x ± h , y ± k) the right arrow symbol used to show the
    translation from a point to its image
    Example:
    ∵ P (0 , 0) → P’ (1 , 2)
    ∴ The rule is (x , y) → (x + 1 , y + 2)
    Let us find the translation rule that maps point D ( 7 , − 3 ) onto
    point D’ (2 , 5)
    ∵ Point (x , y) = (7 , -3)
    ∵ Its image after translation (x + h , y + k) = (2 , 5)
    ∴ x + h = 2
    ∵ x = 7
    ∴ 7 + h = 2
    – Subtract 7 from both sides
    ∴ h = -5
    ∵ y + k = 5
    ∵ y = -3
    ∴ -3 + k = 5
    – Add 3 to both sides
    ∴ k = 8
    ∴ The rule of translation is (x , y) → (x – 5 , y + 8)
    The translation rule that maps point D ( 7 , − 3 ) onto point D ‘ ( 2 , 5 )
    is (x , y) → (x – 5 , y + 8)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )